Combined use of multiparametric flow cytometry and cytomorphology to enhance detection of neuroblastoma metastatic cells in bone marrow. (10th December 2019) - Manenq, Christine; Lesesve, Jean‐François; Dreumont, Natacha; Massin, Frédéric; Salignac, Sylvain; Mansuy, Ludovic; Chastagner, Pascal; Latger‐Cannard, Véronique; Broséus, Julien
Abstract: Introduction: In the context of neuroblastoma (NB), the screening for bone marrow (BM) metastasis is a recurrent issue for hematology laboratory routine practice. Detection of low tumor burden using light microscopy is often difficult. In this regard, our objective was to evaluate the performance of multiparametric flow cytometry (FC) for detecting NB metastatic cells in BM. Methods: We applied a new FC multiparametric panel allowing the analysis of the co‐expression of 5 surface markers: GD2 (disialoganglioside 2), CD9, CD56, CD81, and CD90, on CD45‐negative BM cell populations, and compared results with BM biopsy immunohistochemistry, which is the reference method. Results: In spike‐in tests, the multiparametric FC successfully detected NB cells mixed in peripheral blood mononuclear cells to a level of 0.01%. FC analysis was performed on 45 sets of BM aspirates sampled from 21 children, either at diagnosis or during follow‐up. Combining multiparametric FC with light microscopy improved NB metastasis detection, with a higher sensitivity (76.9% vs 61.5%) and a higher specificity (94.4% vs 77.8%) as compared to light microscopy alone. At the time of diagnosis, multiparametric FC detected NB metastatic cells in all cases. Conclusion: These results illustrate the performance of multiparametric FC analysis to detect metastatic BM infiltration of NB. This is of particular interest in an emergency context, since when combined with light microscopy, it enhances the detection of metastatic invasion within a short timeframe, allowing an adapted and rapid clinical management.